A deployable network with identical triangular panels based on a special twofold-symmetric Bricard 6R linkage. (December 2022) - Gao, Yuan; Yang, Fufu; Chen, Bingxing; Zhang, Jun
Highlights: To propose a one-DOF network with polygon panels forming 3D shapes without membrane. To determine geometric conditions by the compatibility analysis. To evaluate the motion performance by a kinematic analysis and two prototypes. Abstract: Large deployable networks, usually composed of spatial overconstrained linkages, are widely used in engineering for high expansion to package ratio. However, the existing networks always need some deployable membranes, which should be additionally designed and fabricated to form desired 3D shapes due to their rod-shaped components. In this paper, identical triangular panels are considered as components and a deployable network is proposed based on a special twofold-symmetric Bricard 6 R linkage. The proposed network could form prism-like structures without membranes. According to the compatibility of the network, the geometric conditions of the panels are determined, and the folding performance of the network is evaluated by a kinematic study and two physical prototypes. Since rigid panels and only R -joints are utilized, the proposed network exhibits greater rigidity than that with membranes, facilitating mass production in future applications.